Advanced Polycarbonate Transparent Systems with Aerogel: Preliminary Characterization of Optical and Thermal Properties. (May 2017) - Moretti, Elisa; Zinzi, Michele; Carnielo, Emiliano; Merli, Francesca
Abstract: The market penetration of polycarbonate (PC) multi-sheets panels for building applications is increasing due to intrinsic properties of the material: high transparency, reduced weight if compared to glass and competitive costs. The presence of air gaps within the panel assures good thermal insulation; however, to further improve the thermal properties of the component, the air gaps can be filled by granular silica aerogel. These materials are also characterized by high scattering optical properties, so that the incident radiation can be diffused in the built environment, preventing from glare. This paper deals with the characterization of several configurations of PC systems, differing in thickness and geometry. Thermal transmittance measurements were carried out using a guarded hot plate apparatus, according to EN 674:2011. Spectral transmittance and reflectance measurements were carried out by means of a large integrating sphere apparatus, broad-band light and solar quantities were then calculated. A valid data set of product specification is thus provided. The investigated polycarbonate systems could be a valid solution in place of classic windows for non-residential buildings, enhance the thermal insulation and the light control of the building envelope, thus providing improved comfort conditions for occupants.